2013
DOI: 10.1371/annotation/5ec7a768-7129-460f-9290-57ae5d631dd9
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Semen Levels of Spermatid-Specific Thioredoxin-3 Correlate with Pregnancy Rates in ART Couples

Abstract: Spermatid specific thioredoxin-3 (SPTRX3 or TXNDC8) is a testis/male germ line specific member of thioredoxin family that accumulates in the superfluous cytoplasm of defective human spermatozoa. We hypothesized that semen levels of SPTRX3 are reflective of treatment outcome in assisted reproductive therapy (ART) couples treated by in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI). Relationship between SPTRX3 and treatment outcome was investigated in 239 couples undergoing ART at an infert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…On the contrary, mRNA expression of SPTRX-3 in ram testis was again confirmed by PCR analysis ( Appendix A ; Figure A1 ), thus indicating that SPTRX-3, as well as MKRN1 expression, should be assessed also in ram testis and defective spermatozoa using species-specific or cross-reactive antibodies. Moreover, it was demonstrated that higher levels of SPTRX-3 in semen correlate with male infertility [ 37 , 38 ]; therefore, SPTRX-3 might be an important quality indicator of individual ram semen intended for the preservation of genetic resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, mRNA expression of SPTRX-3 in ram testis was again confirmed by PCR analysis ( Appendix A ; Figure A1 ), thus indicating that SPTRX-3, as well as MKRN1 expression, should be assessed also in ram testis and defective spermatozoa using species-specific or cross-reactive antibodies. Moreover, it was demonstrated that higher levels of SPTRX-3 in semen correlate with male infertility [ 37 , 38 ]; therefore, SPTRX-3 might be an important quality indicator of individual ram semen intended for the preservation of genetic resources.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed to accumulate in the superfluous midpiece cytoplasm and nuclear vacuoles of defective human spermatozoa, or in the round testicular spermatids of other mammals. An increased content of SPTRX-3 positive spermatozoa was found in infertile males [ 37 , 38 ]. PAWP, post-acrosomal sheath WW-domain binding protein (known also as WBP2NL), is located in the post-acrosomal region of heads in normal spermatozoa and plays an important role during fertilization in the oocyte activation.…”
Section: Introductionmentioning
confidence: 99%